2010
DOI: 10.1597/08-285.1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Craniomaxillofacial Malformations: A Characterization of Phenotypes in Trisomies 13, 18, and 21 by Ultrasound and Pathology

Abstract: Facial anomalies are common in the major trisomies, and their prenatal sonographic identification should be improved. The above-mentioned facial anomalies provide sufficient reason to consider performing cytogenic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In fact, compared with Trisomy 18 and Trisomy 21, Trisomy 13 was found to be highly associated with craniomaxillofacial malformations. This was confirmed, through prenatal sonographic imaging, by Ettema [37], as particularly evident in cleft deformities (76.9%). Similarly, Tolarova, Shaw and Genisca [9, 12, 22], reported a congruous higher rate of clefts, mostly CL/P, in infants with Trisomy 13.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, compared with Trisomy 18 and Trisomy 21, Trisomy 13 was found to be highly associated with craniomaxillofacial malformations. This was confirmed, through prenatal sonographic imaging, by Ettema [37], as particularly evident in cleft deformities (76.9%). Similarly, Tolarova, Shaw and Genisca [9, 12, 22], reported a congruous higher rate of clefts, mostly CL/P, in infants with Trisomy 13.…”
Section: Discussionmentioning
confidence: 56%
“…Although fetal external ear abnormalities belong to minor physical anomalies, developmental anomalies of the external ear are still be found in some genetic diseases such as trisomy 21 and trisomy 18 [2629]. Previous studies have confirmed that anomalous, low-set, and malformed ears are one of the common symptoms of chromosomal abnormalities; for instance, ear abnormalities are often linked with trisomy 9 (chromosome 9 abnormality), Edwards syndrome/trisomy 18 (chromosome 18 abnormality), Patau syndrome (chromosome 13 abnormality), Down syndrome (chromosome 21 abnormality), Cri du chat/chromosome 5q deletion syndrome, CHARGE (chromosome 8 abnormality), trichorhinophalangeal syndrome, Type 1 (chromosome 8 abnormality), Beckwith-Wiedemann (chromosome 11 abnormality), Jacobsen syndrome (chromosome 11 abnormality), Smith-Magenis syndrome (chromosome 17 abnormality), Emanuel syndrome (chromosome 11 and/or 22 abnormality), Turner syndrome (chromosome XO or mosaic XX/X0 abnormality), Triple X syndrome (chromosome 49 and/or XXXXX abnormality), and so forth [30] (see Table 2).…”
Section: Discussionmentioning
confidence: 99%